Mengintegrasikan Pendidikan dengan Perjuangan: Peran Teungku Chik Muhammad Amin - Mardhiah, Ainul; Badawi, Afif; Mutia, Mutia; Ahmad, Syafiqah Solehah Binti (Desultanah: Journal Education and Social Science, 2025)
This study examines the role of Teungku Chik Muhammad Amin in integrating Islamic education with the struggle against Dutch colonialism in Aceh through Dayah Cot Kala. The lack of specific studies on the integration of education and struggle during the war in Aceh is the purpose of this research, so that this research can complement the previous study on Teungku Chik Muhammad Amin. This study aims to analyze the role of Teungku Chik Muhammad Amin who has combined the teaching of religious science with resistance strategies and formed socio-political awareness among students. The method used is Systematic Literature Review (SLR) to collect and analyze relevant literature in a systematic manner. The results show that Teungku Chik Muhammad Amin succeeded in instilling the value of jihad and fighting spirit, trained military tactics, and built the character of socio-politically conscious scholars-fighters, making education in dayah a strategic base for the resistance of the Acehnese people. Therefore, it can be concluded that the integration of education and struggle made an important contribution to the history of Islamic education and the resistance of Aceh.